Oral health of elderly people living in a rural community of slave descendants in Brazil - Luiza Fernandes Fonseca Sandes; Daniel Antunes Freitas; Maria Fernanda Neves Silveira de Souza (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2018)
Abstract Background Oral health has an important impact on quality of life and should be an integral part of the overall health of the individual. Quilombolas, afro-descendants communities, live in difficult-access rural areas and with several obstacles on the use of health services. Objective This study is aimed to analyse the oral health conditions of the older Quilombola population in the North of Minas Gerais, Brazil, and the main limitations faced by these communities regarding public health services' access. Method This study evaluated the oral health of elderly Quilombola population in the North of Minas Gerais, Brazil. The study's population consisted in 669 Quilombolas, aged 65 to 74 years old, residing in 33 Quilombola rural communities that are located in 20 different counties of Brazil. Examinations and interviews were conducted in the houses of the elderly people surveyed for the assessment of oral health condition, analysing the use of dental health services, objective conditions (clinical) and subjective conditions (reported). Results Most of the interviewees were self-declared black, female, illiterate and living below the minimum wage. More than 50% of the elderly Quilombola- population interviewed were edentulous and only 17% used total prosthesis. The smiling was the main impact of oral condition reported by them in everyday life. Conclusion The analysis provided by this study exposes the impact of overlooked oral health conditions in minority populations as Quilombolas and reinforces the need of public investments in those vulnerable communities.